Information model of registration and analysis of technological factors arising during final processing of products of transport pipeline systems - Kotukh, Volodimir; Kaptsova, Nataliy; Pakhomov, Yuriy; Kosenko, Vitaliy (International Journal of Engineering and Technology, 2018)
One of the most important technological characteristics of the rubbing surfaces of the shut-off part of the pipe fittings (PF) of the transport pipeline systems (TPS) is their waviness, which is characterized by the deviation of the step of the wave to the height of the micro-roughness. The nature of the waviness is associated with oscillations of the working bodies of the executive devices of the technological equipment in the production process of manufacturing or repairing precision pairs of PF. The waviness of the rubbing surfaces of the PF shut-off part, as well as the high accuracy of their processing, is achieved by increasing the kinematic stiffness of the process equipment, as well as improving the methods and means for the precise processing of the PF precision pairs.Â Â